2015
DOI: 10.3358/shokueishi.56.228
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Seven Fungicides in Citrus Fruits

Abstract: A rapid and simple determination method of seven fungicides, thiabendazole TBZ , pyrimethanil PYR , o-phenylphenol OPP , fludioxonil FLD , azoxystrobin AZX , imazalil IMZ and diphenyl DP in citrus fruits by LC-MS and HPLC-FL was developed. The seven fungicides were extracted with acetonitrile from citrus fruits and cleaned up with Z-Sep/C18 cartridges. The LC separation was performed on a phenyl-hexyl column with methanol-acetonitrile-10 mmol/L ammonium formate 10 : 35 : 55 as a mobile phase. The recoveries fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Yoshioka et al 3) reported that the sensitivities for DP and OPP were low on LC-MS (ESI) analysis, so they determined these two fungicides by HPLC equipped with a fluorescence detector, while AZO, FLUDI, IMZ, PYRI and TBZ were analysed by LC-MS. However, the sensitivities for AZO and FLUDI also seemed to be insufficient for application in real matrices.…”
Section: Gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshioka et al 3) reported that the sensitivities for DP and OPP were low on LC-MS (ESI) analysis, so they determined these two fungicides by HPLC equipped with a fluorescence detector, while AZO, FLUDI, IMZ, PYRI and TBZ were analysed by LC-MS. However, the sensitivities for AZO and FLUDI also seemed to be insufficient for application in real matrices.…”
Section: Gc-msmentioning
confidence: 99%
“…1. Although Yoshioka et al 3) recently reported determination methods for AZO, FLUDI, IMZ, PYRI and TBZ by LC-MS and for DP and OPP by HPLC, a GC-MS method could monitor all seven fungicides in a single run. Therefore, we developed a GC-MS method for simultaneous identification and quantification of these fungicides and confirmed its suitability for the determination of the fungicides in citrus fruits.…”
Section: Introductionmentioning
confidence: 99%